Tingkat Kepuasan Pasien Rawat Jalan terhadap Pelayanan Kefarmasian di Puskesmas Oesapa Kota Kupang - Karolina Lawan; Petrus Romeo; Rina Waty Sirait (Universitas Nusa Cendana, 2022)
Service quality is an element that can affect patient satisfaction while undergoing health services at the publich health center. To achieve the quality of service, the effectiveness of achieving its goals will be judged by how good the quality of services is. Patient satisfaction in health services is measured by five indicators, namely reliability, responsiveness, assurance, empathy and appearance. These five aspects are closely related to humans as service providers, so that the assessment of the level of satisfaction is very subjective both from the perspective of the community (patiens) and aspect of the assesment. The purpose of this study was to determine the satisfaction of outpatiens with pharmaceutical services at the public health center Oesapa. The method used in this research is descriptive analytic. The sample in this study amounted to 100 people. The sampling technique used an accidental sampling approach. The results showed that the sub-variable level of patient satisfaction on the realibility dimension was included in the satisfie category (75,65%), the empathy dimension was included in the quite satisfied category (60,06%), the responsiveness dimension was included in the quite satisfied category (60,70%), the assurance dimension is included in the satisfied category (78,10%), and the appearance dimensionis includedin the satisfied category (78,70%).